DINAMIKA PERKEMBANGAN HIV/AIDS DI KABUPATEN KUDUS MENGGUNAKAN MODEL PERSAMAAN DIFERENSIAL NONLINEAR SIR (SUSCEPTIBLE, INFECTIOUS AND RECOVERED) - Ivanna Isty Nursani; Nur Alisa; Irma Latifah; Melvin Dewi Rosita (Universitas Muhammadiyah Kudus, 2023)
HIV/AIDS is the Human Immunodeficiency Virus, or HIV is often abbreviated as a deadly virus from two lentivirus species that cause it. The virus attacks humans and attacks the immune system, so that the body becomes weak in fighting infection. HIV/AIDS will also occur in Kudus Regency in 2021, there will be an additional 124 cases of HIV/AIDS sufferers in Kudus. But for this year, from January to October 2022, the number of confirmed cases has grown by 184. Head of Disease Prevention and Control, Kudus District Health Office (DKK), Darsono, said the phenomenon of the rise of 'open BO' was one of the factors for the rapid growth of HIV/AIDS cases. Therefore, a study was conducted to determine the dynamics of HIV/AIDS development in Kudus District using the SIR nonlinear differential equation model. The data used is data on the number of people living with HIV/AIDS and the total population in Kudus Regency for 2020 – 2021 from the Central Statistics Agency and the Kudus District Health Office. In this study, it was concluded that there would be an epidemic of HIV/AIDS in a period of up to 50 years.